Analisa Penerimaan Aplikasi Mypertamina dengan Model Unified Theory of Acceptance and Use of Technology 2 dan Information Systems Success Model - Mangapul Siahaan; Suwarno Suwarno; Chintya Lorenz (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the factors that influence the acceptance of the MyPertamina application in Batam City using the UTAUT2 model approach and the IS Success Model. This research model includes variables such as performance expectancy, effort expectancy, hedonic motivation, facilitating conditions, information quality, system quality, service quality, behavioral intention, user satisfaction, and use behavior. Data were collected from 177 respondents who used the MyPertamina application in Batam City and analyzed using the PLS-SEM and SEM (Amos) methods. The results showed that factors such as performance expectancy, effort expectancy, supporting conditions, information quality, service quality, user satisfaction, and behavioral intention had a significant influence on the acceptance of the MyPertamina application. In contrast, hedonic motivation and system quality did not show a significant influence. This study provides important insights into the factors that influence the acceptance of technology-based applications and provides recommendations for the development of similar applications in the future.